Reconhecimento internacional da economia social e solidária frente aos desafios da promoção dos objetivos do desenvolvimento sustentável: um estudo de caso sobre a atuação da força-tarefa interagências da ONU - Aragão, Nathalia Oliveira Palitot (2024)
The global dilemmas of biodiversity preservation, addressing the climate crisis, eradicating poverty and hunger, promoting peace, empowering women, implementing technological innovations, increasing the number of jobs, and improving quality of life, among many other challenges, are addressed in the 2030 Agenda. The means of continuously improving sustainable development processes generate discussions and alignments on a global scale, as the assets involved are not of a private or merely domestic nature, affecting nations spread across the entire globe. Therefore, public policies with the potential to promote sustainable development deserve to be studied. In this case, the correlation between the Social and Solidarity Economy and the referred UN development agenda is addressed. Thus, this study aims to analyze the role of the United Nations InterAgency Task Force (UNTFSSE) in the international recognition of the social and solidarity economy as a promoter of sustainable development, especially SDG 8, which seeks to foster sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all. From a methodological standpoint, a qualitative approach was used, with this research being classified as basic and exploratory, materializing technically as a case study. To achieve the objectives of this study, different data collection techniques were mobilized. Thus, to present the international context of the development agenda, a bibliographic review and document analysis were used. To map the documents produced by the ILO and the UN from 2013 to 2023 on the Social and Solidarity Economy in the context of decent work, document analysis was used. Finally, to investigate the role of the Inter-Agency Task Force, semi-structured interviews and document analysis were employed. The analysis carried out allows us to affirm that the advocacy actions of the Task Force, including facilitating intergovernmental dialogues, drafting strategic recommendations, participating in global events, and creating documents and courses, have been decisive in promoting the international recognition of the SSE as a public policy of singular importance for the sustainable development agenda.